Ocean Acidification as a Governance Challenge in the Mediterranean Sea: Impacts on Aquaculture and Fisheries - Bednarsek, Nina; Guilloux, Bleuenn; Canu, Donata Melaku; Galdies, Charles; Guerra, Roberta; Simoncelli, Simona; Feely, Richard; Pelletier, Greg; Gašparović, Blaženka; Godrijan, Jelena; Malej, Alenka; Solidoro, Cosimo; et al. (CCSD, 2023)
International audience Abstract Despite the progress in the international and regional governance efforts at the level of climate change, ocean acidification (OA) remains a global problem with profoundly negative environmental, social, and economical consequences. This requires extensive mitigation and adaptation effective strategies that are hindered by current shortcomings of governance. This multidisciplinary chapter investigates the risks of ocean acidification (OA) for aquaculture and fisheries in the Mediterranean Sea and its sub-basins and the role of regional adaptive governance to tackle the problem. The identified risks are based on the biological sensitivities of the most important aquaculture species and biogenic habitats and their exposure to the current and future predicted (2100) RCP 8.5 conditions. To link OA exposure and biological sensitivity, we produced spatially resolved and depth-related pH and aragonite saturation state exposure maps and overlaid these with the existing aquaculture industry in the coastal waters of the Mediterranean basin to demonstrate potential risk for the aquaculture in the future. We also identified fisheries’ vulnerability through the indirect effects of OA on highly sensitive biogenic habitats that serve as nursery and spawning areas, showing that some of the biogenic habitats are already affected locally under existing OA conditions and will be more severely impacted across the entire Mediterranean basin under 2100 scenarios. This provided a regional vulnerability assessment of OA hotspots, risks and gaps that created the baseline for discussing the importance of adaptive governance and recommendations for future OA mitigation/adaptation strategies. By understanding the risks under future OA scenarios and reinforcing the adaptability of the governance system at the science-policy interface, best informed, “situated” management response capability can be optimised to sustain ecosystem services.